2022
DOI: 10.3390/bs12020051
|View full text |Cite
|
Sign up to set email alerts
|

Trust, Media Credibility, Social Ties, and the Intention to Share towards Information Verification in an Age of Fake News

Abstract: Social media is now the primary form of communication between internet users and has soared in popularity, which has directly impacted the spread of the phenomenon of fake news. Fake news is not only a widespread phenomenon; it is also problematic and dangerous for society. The aim of this study is to understand the phenomenon of fake news better. The study utilised a structural modelling equation in order to identify how Polish society perceives the problem of fake news and assess the extent to which it trust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 56 publications
2
10
0
Order By: Relevance
“…al, 2021. Similarly, recent research consistent with this finding found that fake news awareness negatively effecting the perceived credibility on social media (Majerczak & Strzelecki, 2022).…”
Section: Research Model and Hypotheses Developmentsupporting
confidence: 77%
“…al, 2021. Similarly, recent research consistent with this finding found that fake news awareness negatively effecting the perceived credibility on social media (Majerczak & Strzelecki, 2022).…”
Section: Research Model and Hypotheses Developmentsupporting
confidence: 77%
“…These findings are explicable considering the current climate of misinformation and disinformation on social media platforms, which makes it increasingly difficult for people of all ages to discern between fact and fiction [ 108 , 109 ]. Numerous previous studies have been conducted on social media sharing [ 10 , 110 , 111 ] in the context of proliferation of news on social media [ 112 ]. Users share information that they perceive valuable or personal [ 113 ].…”
Section: Discussionmentioning
confidence: 99%
“…Prior research has discussed various factors that influence news verification behavior among users. These include fake news awareness, trust in the source, and media credibility (Majerczak and Strzelecki, 2022;Pundir et al, 2021;Torres et al, 2018). Yet, cognitive biases in information processing limit individuals' intent to verify information (Edgerly et al, 2020).…”
Section: Mediating Role Of Intention To Verify Political Deepfake Videomentioning
confidence: 99%
“…Prior research has discussed various factors that influence news verification behavior among users. These include fake news awareness, trust in the source and media credibility (Majerczak and Strzelecki, 2022; Pundir et al. , 2021; Torres et al.…”
Section: Hypothesis Developmentmentioning
confidence: 99%